IMPLEMENTASI GREEN HUMAN RESOURCE MANAGEMENT DALAM USAHA MIKRO KECIL MENENGAH PENGOLAHAN SEAFOOD BERKELANJUTAN: STUDI KASUS KOMUNITAS BUDIDAYA RUMPUT LAUT DI KABUPATEN SERANG, BANTEN - Hisyam, Muhammad Rizki Zul; Aulia, Dita Aulia; Haris, Ruli; Mahera, Liza (LPPM Universitas Banten jaya, 2026)
This research explores the implementation of Green Human Resource Management (GHRM) practices in sustainable seafood small and medium enterprises (SMEs) operating within seaweed cultivation communities in Serang Regency, Banten. Through qualitative methodology employing embedded case study design, the research involved 38 respondents during March–December 2024, combined with focus group discussions (3 sessions), 120 hours of participatory observation, and analysis of 73 organizational documents. Findings reveal that despite limited formal HRM infrastructure, seaweed farming communities implement emergent GHRM practices rooted in systematic integration of local ecological knowledge and community-based management traditions. The research identifies three primary dimensions of implementation: (1) green environmental management practices encompassing water quality monitoring, waste management, and ecosystem conservation; (2) green human development practices integrated within continuous training and environmental awareness; and (3) green organizational culture embedded in traditional coastal community values and participatory decision-making. Analysis using the Ability-Motivation-Opportunity (AMO) framework demonstrates that GHRM effectiveness depends on alignment between technical environmental capability building, structuring of economic incentives for sustainable behavior, and creation of participatory opportunities in environmental decision-making. The research identifies significant barriers including limited technical and financial capacity, minimal access to green certification training, and gender inequality in employment placement. The research proposes a contextually-adapted GHRM framework for informal SME contexts, emphasizing capacity building with integration of indigenous knowledge systems and coordinated institutional support. The research contributes to understanding GHRM implementation in informal SME contexts within developing economies and demonstrates the relevance of indigenous management approaches in achieving sustainable development objectives.